Incentive mechanism of public servants in Kazakhstan: evaluation and ways for its development - K., *Shedenov O.; U., Shedenova N. (Farabi Journal of Social Sciences, 2019)
Abstract. The paper aimsto research about motivation levels of public servants in Republic of Kazakhstan and to propose ways for its development as the main factor of effectiveness of public service.The aspects explored are the methods and techniques required to evaluate public servants and the quality of their work according to the principles of equity and justice.